-3s-11=s+-9

Simple and best practice solution for -3s-11=s+-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3s-11=s+-9 equation:



-3s-11=s+-9
We move all terms to the left:
-3s-11-(s+-9)=0
We add all the numbers together, and all the variables
-3s-(s-9)-11=0
We get rid of parentheses
-3s-s+9-11=0
We add all the numbers together, and all the variables
-4s-2=0
We move all terms containing s to the left, all other terms to the right
-4s=2
s=2/-4
s=-1/2

See similar equations:

| (7q-46)+3q+6=180 | | 5x+12=7÷6x+12=8 | | -2+16=m-2 | | (2x+7)+(4x-14)=180 | | 15-4n=81 | | 3(x-2)+6=x+2(5+4) | | y-5/11=2 | | 2(8-3x)-2(2x+9)=x-12 | | 5x+10x+36.5=180 | | 42-2x=3 | | 5x+7x+36.5=180 | | 5x/9-1/3=3 | | 5x+3x+36.5=180 | | 0.15x+25=26 | | 11/20=x/160 | | 5x+4x+36.5=180 | | -8k+(3-4k)8=104- | | 5x=-15* | | x-5x+7=2x-14 | | 2(6-2x)-3(4x+6)=x-11 | | x/2+1/2=1 | | 0.04x+0.07(10,000.00-x)=600.00 | | 3x-31=-(10/x) | | 6u+41=-5(u+5) | | X/5+2/5=x/5+2/5 | | 900-700=0.03x | | 700-900=0.003x | | 1-2x=-8-5x | | 3x*(2x+1)=3x-12 | | 100=5t | | 2x-8+4x+10=180 | | -28=7y+5(y-8) |

Equations solver categories